2022
DOI: 10.1002/ldr.4375
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agriculture intensification on forest degradation and tree carbon stock; promoting multi‐criteria optimization for restoration in Central India

Abstract: Forest conservation entails both halting destruction and protecting the state of the forest's vegetation. Monitoring forest cover and restoring degraded forests are critical ecological aspects for India's forestry sector's long‐term growth. Cropland expansion and intensification are the primary approaches for increasing agricultural productivity in response to increased biomass demand, but they are also major drivers of biodiversity loss. We evaluated the ecosystem carbon (C) stock and sequestration potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…31.63% of total vegetation biomass in comparison to reference forest, and this reduction was positively correlated with standing stock, basal area, and plant diversity. A second study also found significant positive correlation between disturbance levels and overall carbon stock in dry deciduous forest of central India (Shukla et al, 2022).…”
Section: Forest Degradationmentioning
confidence: 77%
See 2 more Smart Citations
“…31.63% of total vegetation biomass in comparison to reference forest, and this reduction was positively correlated with standing stock, basal area, and plant diversity. A second study also found significant positive correlation between disturbance levels and overall carbon stock in dry deciduous forest of central India (Shukla et al, 2022).…”
Section: Forest Degradationmentioning
confidence: 77%
“…They report that disturbed forest lost 31.63% of total vegetation biomass in comparison to reference forest, and this reduction was positively correlated with standing stock, basal area, and plant diversity. A second study also found significant positive correlation between disturbance levels and overall carbon stock in dry deciduous forest of central India (Shukla et al, 2022). Researchers argue this rapid loss of forests needs priority for reduction and reversal by appropriate site‐specific restoration.…”
Section: Review Of Papers Published In This Issuementioning
confidence: 91%
See 1 more Smart Citation